The Revolutionary Global Islamism – Politicized or Political Religion? Applying Eric Voegelin’s Theory to the Dynamics of Political Islam - Miliopoulos, Lazaros (Religion compass, 2013)
In recourse to the theory of fundamentalism Islamism can be defined as a form of "other" or "halved modernity." Therefore Islamism politicizes the understanding of Islam and has been described often as a ‘politicized religion’. But it is further be necessary to differentiate clearer between Islamist tendencies of traditionalism and totalitarianism: On the one hand there is the aim to restore the ‘naturalness’ and purity of a pre-modern, monistic world. On the other the ideology of a specific revolutionary type of Islamism can be described partially as totalitarian, gnostic and messianic or defined as a ‘modern political pseudo-religion’, diametrically opposite to the spirit of the traditional religions such as Christianity, Judaism or Islam itself and rather comparable with ideologies such as Marxism-Leninism, Fascism and National Socialism. To answer the question whether the revolutionary Islamism is a politicized or political (pseudo-)religion, this essay applies Eric Voegelin’s Theory of ‘political religion’ to the revolutionary global Islamism expressed by the al-Qaeda terrorist movement.